How prescribers can use technology to improve patient care. (2nd April 2019) - Shah, Sam; Coughlan, James
Abstract : Health information technologies (HITs) have become increasingly used in the NHS and offer prescribers the opportunity to prescribe in a more consistent and reliable way. There is a growing use of electronic prescribing systems, especially in primary care. This will likely reduce prescription errors, but evidence is unclear if it will improve patient outcomes. Clinical decision support systems can reduce variability and alert clinicians when prescriptions could cause patients harm; however, automation bias can create new errors to prescribers who over-rely on the system. HITs can better communication by improving discharge letters, facilitating telehealth appointments and supporting those working in remote settings. Mobile apps offer a way to engage patients in their own care and allow remote monitoring of chronic conditions in primary care, and acute conditions in emergency care settings. There are challenges in realising these benefits, with inconsistent infrastructure and a 10-year delay in realising predicted efficiency savings.